Formas combinantes: un estudio sobre los procesos morfológicos de truncamiento en español - Cantero, Mónica (2004)
This work will consider two important points in the Spanish morphology. First, to contribute an adapted description for a series of words that appears to be between affixation and composition. Second, thanks to this description, it will show the relevance that the morphologic process of secretion and its units (combining forms) have in the creation of new words in the Spanish lexicon. Also, this morphological process of secretion is a clear reflection of the pragmatic motivations used by the speakerlistener of a language with the purpose of manipulating morphologic processes and creating from this manner a new lexicon and linguistic connotations in the language.